Strategies to improve PrEP uptake among West African men who have sex with men: a multi-country qualitative study - Reyniers, Thijs; Babo, Stéphane Alain Yoro; Ouedraogo, Mamadou; Kanta, Ibrahima; Ekon Agbégnigan, Laurette; Rojas, Daniela; Eubanks, August; Anoma, Camille; Dah, Ter Tiero Elias; Mensah, Ephrem; Dembélé Keita, Bintou; Spire, Bruno; et al. (Frontiers in Public Health, 2023)
Introduction West African men who have sex with men (MSM) remain at substantial risk of contracting HIV. Pre-exposure prophylaxis (PrEP) can be an effective game-changer in reducing the number of HIV infections in MSM communities. To optimize the roll-out of PrEP, we need to better understand how we can increase its uptake. The objective of this study was to explore the perceptions of West African MSM toward PrEP and their proposed strategies to overcome barriers to PrEP uptake within their communities. Methods Between April 2019 and November 2021, we conducted 12 focus group discussions with 97 MSM not taking PrEP, and 64 semi-structured interviews with MSM taking PrEP, in Burkina Faso, Côte d'Ivoire, Mali, and Togo. Data collection and analysis were guided and conducted by local research teams, enabling a community-based participatory approach. A coordinating researcher collaborated with these local teams to analyze the data guided by a grounded theory approach. Results The results show that participants were generally positive toward PrEP and that MSM communities have become more aware of PrEP for the study. We identified three main strategies for increasing PrEP uptake. First, participants proposed to raise awareness and improve knowledge of HIV as they considered the self-perceived risk of MSM in their communities to be low. Second, because of existing misconceptions and false information, participants proposed to improve the dissemination of PrEP to allow for informed choices, e.g., via peers or PrEP users themselves. Third, as oral PrEP also entails a risk of being associated with HIV or homosexuality, strategies to avoid stigmatization (e.g., hiding pills) were deemed important. Discussion These findings indicate that the roll-out of oral PrEP and other future PrEP modalities should be accompanied by raising awareness and improving knowledge on HIV, and wide dissemination of information that focuses on the health-promoting aspect of these tools. Tailored delivery and long-acting PrEP modalities will be important to avoid potential stigmatization. Sustained efforts to prevent discrimination and stigmatization based on HIV status or sexual orientation continue to be highly important strategies to address the HIV epidemic in West Africa.